GAMBARAN KEPATUHAN PERAWATAN KAKI PADA PENDERITA DIABETES MELLITUS DI PUSKESMAS SUKOSEWU KABUPATEN BOJONEGORO - Susanti, Dwi Agung (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2018)
Diabetes mellitus (DM) is a collection of symptoms that arise in a person who caused an increase in blood glucose levels. Uncontrolled diabetes mellitus with chronic complications will be either a diabetic ulcer occurred IE. One of the preventive efforts in patients of diabetes mellitus are foot care compliance to reduce the occurrence ofdiabetic ulcer complications. This research aims to know the compliance of foot carein diabetics mellitus in Bojonegoro Regency Sukosewu Clinics.This research uses descriptive method, with an entire population of people with diabetes mellitus, as many as 50 people, while the sampelnya as many as 30 people, with sampling purposive sample makers. How data retrieval with a questionnaire which is then processed by means of editing, coding, skoring, tabulating presented in the form of a frequency table is confirmed with a percentage and narrative.The research results of the 30 respondents in Bojonegoro Regency Sukosewu the majority of clinics that is as many as 30 people (100%) did not comply in performing foot care.Conclusion the majority of respondents are not obedient in doing foot care. For that the respondents need to check walk every day and do your foot care whenever regularly 2 times a day (every bathroom runs out), and the patient must comply with the officer's advice against health.